2010
DOI: 10.1093/jxb/erq054
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of apomixis-linked alleles revealed by comparative transcriptomic analysis of sexual and apomictic Paspalum simplex Morong flowers

Abstract: Apomixis is defined as clonal reproduction by seed. A comparative transcriptomic analysis was undertaken between apomictic and sexual genotypes of Paspalum simplex Morong to identify apomixis-related polymorphisms at the level of mRNA. cDNA-AFLP (amplified fragment length polymorphism) profiling of apomictic and sexual flowers at several stages of development yielded 202 amplicons that showed several kinds of expression specificities. Among these, the large majority consisted of amplicons that were present onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 51 publications
2
94
0
1
Order By: Relevance
“…These play crucial roles in auxin-regulated gene expression, for example to control cell type-specific auxin responses during Arabidopsis embryo development [76], [77]. Evidence for differential expression of ARF genes has previously been reported during early stages of reproductive development in a comparative cDNA-AFLP analysis targeting sexual and apomictic Paspalum simplex flowers [35].…”
Section: Discussionmentioning
confidence: 97%
“…These play crucial roles in auxin-regulated gene expression, for example to control cell type-specific auxin responses during Arabidopsis embryo development [76], [77]. Evidence for differential expression of ARF genes has previously been reported during early stages of reproductive development in a comparative cDNA-AFLP analysis targeting sexual and apomictic Paspalum simplex flowers [35].…”
Section: Discussionmentioning
confidence: 97%
“…In the past few years, several studies have been published which identify transcripts that are differentially expressed in reproductive tissues of apomictic and sexual plants (Rodrigues et al 2003;Albertini et al 2004;Laspina et al 2008;Cervigni et al 2008;Yamada-Akiyama et al 2009, Polegri et al 2010. All these articles were focused on the characterization of protein-coding transcripts and presented valuable evidence indicating that central pathways (i.e., ERK signaling, protein degradation, RNA transcription and DNA modification) were differentially modulated in agamospermic plants with respect to sexual ones.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences with similar annotations have been reported to be associated with apomixis and/or polyploidy for various other species, including Poa pratensis [53], Paspalum notatum [44,45], potato [54], Pennisetum squamulatum and Cenchrus ciliare [25], Panicum maximum [55], and Paspalum simplex [24,56]. Taking into account our previous results in E. curvula [32,33,35], the results of the present study, and those reported for other species by other authors, there are many commonalities among the different species with respect to apomixis.…”
Section: Validation Of Gene Expression By Real-time Pcrmentioning
confidence: 82%